The chain reaction between the media and sport. The impact of rule changes in handball - Marczinka, Z.; Gál, A. (Physical Culture and Sport. Studies and Research, 2018)
A long, historical cooperation exists between sport and the media. The media can lift up the profile of a sport, and sport provides a marketable topic/product to talk about. Rules have been changed and playing conditions adapted to add to the glamor and spectacle of sport, thus making sport more marketable, enhancing media coverage and making it more appealing for the viewer. In the history of handball, rule changes have been introduced for the same purpose. However, changing the rules has a great effect on the team`s performance, and thus on the coaches` work as well. There is no doubt that among the rule modifications introduced by the International Handball Federation (IHF) in 2016, substituting the goalkeeper for another court player during an attack without wearing a special shirt has had the greatest impact on the game in recent times. The main aim of the study was to carry out empirical research in order to analyze the recent rule modifications by the IHF, particularly when substituting the goalkeeper for an extra court player during an attack. The 2017 World Championship in France provided an ideal opportunity to collate data in order to explore how often and effectively teams used this rule change at the latest world event. In addition, we have also sought out the opinions of elite coaches concerning the state of current rules in handball and what they would change in order to make this sport discipline more marketable for the media and for spectators. The results show that teams substituted their goalkeeper for an extra court player when in numerical inferiority on average twice as much as when in numerical superiority and on average twice as often when losing as when winning. Surprisingly, the teams` average scoring effectiveness was a little bit higher than when they played in numerical superiority or with an evenly reduced number of players. In addition, the outcome of focus group interviews shows that most coaches think that measuring the attacking time, introducing the third referee into the game, and having better judgment concerning the fast start-off is necessary for the betterment of the game.